2017
DOI: 10.3390/nu9030293
|View full text |Cite
|
Sign up to set email alerts
|

Hypocholesterolemic Effects of Probiotic Mixture on Diet-Induced Hypercholesterolemic Rats

Abstract: Growing evidence has indicated that supplementation with probiotics improves lipid metabolism. We aimed to investigate the beneficial effects of a probiotics mixture (PM) of three strains belonging to the species Bifidobacterium (B. longum, B. lactis, and B. breve) and two strains belonging to the species Lactobacillus (L. reuteri and L. plantarum) on cholesterol-lowering efficacy in hypercholesterolemic rats. A hypercholesterolemic rat model was established by feeding a high-cholesterol diet for eight weeks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 31 publications
9
55
0
Order By: Relevance
“…Although pharmacological drugs for treating hypercholesterolemia conditions are available, oral administration of probiotics has been shown to significantly reduce/prevent serum cholesterol levels in experimental animals . While several in vitro studies on cholesterol removal by probiotics propose diverse mechanisms, in vivo studies in recent years have reported the involvement of probiotics in regulating cholesterol synthesis related proteins and pathways (sterol regulatory element‐binding protein 1 (SREBP1), fatty acid synthase (FAS), acetyl‐CoA carboxylase (ACC) and Niemann–Pick C1‐like 1 (NPC1L1)) in the liver . As shown in these studies, our results demonstrate a diminution in TGL, LDL and total serum cholesterol and an increase in HDL, indicating the involvement of L. fermentum test strains in the regulation of cholesterol absorption related genes and/or pathways.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Although pharmacological drugs for treating hypercholesterolemia conditions are available, oral administration of probiotics has been shown to significantly reduce/prevent serum cholesterol levels in experimental animals . While several in vitro studies on cholesterol removal by probiotics propose diverse mechanisms, in vivo studies in recent years have reported the involvement of probiotics in regulating cholesterol synthesis related proteins and pathways (sterol regulatory element‐binding protein 1 (SREBP1), fatty acid synthase (FAS), acetyl‐CoA carboxylase (ACC) and Niemann–Pick C1‐like 1 (NPC1L1)) in the liver . As shown in these studies, our results demonstrate a diminution in TGL, LDL and total serum cholesterol and an increase in HDL, indicating the involvement of L. fermentum test strains in the regulation of cholesterol absorption related genes and/or pathways.…”
Section: Discussionsupporting
confidence: 84%
“…10 While several in vitro studies on cholesterol removal by probiotics propose diverse mechanisms, 10 in vivo studies in recent years have reported the involvement of probiotics in regulating cholesterol synthesis related proteins and pathways (sterol regulatory element-binding protein 1 (SREBP1), fatty acid synthase (FAS), acetyl-CoA carboxylase (ACC) and Niemann-Pick C1-like 1 (NPC1L1)) in the liver. 24,32 As shown in these studies, our results demonstrate a diminution in TGL, LDL and total serum cholesterol and an increase in HDL, indicating the involvement of Administration of L. fermentum decreases the plasma cholesterol and triglyceride levels while increasing the HDL level. The whole blood levels of toxicological key enzymes (SGPT, SGOT, ALD and ALP) as well as glucose, chloride and urea do not differ significantly between the control and the L. fermentum administered groups (P > 0.05).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Studies have also observed a decrease in water consumption at least partly as a result of the low palatability of Cr (VI) and the toxic effects of the metal . We did not observe changes in water intake in groups supplemented with probiotics, which was also reported by Kim et al …”
Section: Discussionsupporting
confidence: 90%
“…26 Studies have also observed a decrease in water consumption at least partly as a result of the low palatability of Cr (VI) 18,27 and the toxic effects of the metal. 17 We did not observe changes in water intake in groups supplemented with probiotics, which was also reported by Kim et al 28 The increase in the relative weight of the liver may be a result of the toxic effect of Cr (VI) 17,18 that caused hepatomegaly. 29 Intoxication induced by increasing doses of Cr (VI) resulted in liver dysfunction, which was reflected by an alteration in several functional markers in serum and the histological analyses.…”
Section: Discussionsupporting
confidence: 69%